Chapter Water circulation in coastal marine areas - case studies - di natale, michele (Proceedings e report, 2020)
Experimental tests in a physical model have been made to evaluate water circulation within the marinas and over the defence works. The aim of the experimental survey was that of assessing the water circulation intensity behind the works of Salerno and Ischitella coast and inside Fiumicino, Manfredonia and Castelvolturno port. The water circulation over the defense works was evaluated with reference to the storms, while inside marina to the action of the jet mixers. The results of tests show that water circulation is ensured by jet mixer inside marina and by storms behind defence works.